2006
DOI: 10.1017/s0142716406060309
|View full text |Cite
|
Sign up to set email alerts
|

Speech patterns in Cypriot-Greek late talkers

Abstract: The investigation longitudinally examined the phonetic skills of Cypriot-Greek children with late onset of expressive vocabulary. The rate of phonological development within short time increments and the identification of possible speech constraints motivating slow development of expressive language were examined. Participants were seven Cypriot-Greek children identified as late talkers, and seven age-matched normally developing counterparts. Phonetic skills were examined at ages 30, 33, and 36 months for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
3
29
0
1
Order By: Relevance
“…It was noted that the current results corroborate a considerable body of evidence regarding persistent language delay at later developmental age points in LT populations especially from English data pools. In addition, the expressive vocabulary data agree with findings from a number of languages including Dutch, Swedish, Finnish and Greek [4,9,10,29,31,32]. It is concluded that, at least for one linguistic parameter such as expressive vocabulary, persistent delay is a robust phenomenon regardless of mother tongue.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It was noted that the current results corroborate a considerable body of evidence regarding persistent language delay at later developmental age points in LT populations especially from English data pools. In addition, the expressive vocabulary data agree with findings from a number of languages including Dutch, Swedish, Finnish and Greek [4,9,10,29,31,32]. It is concluded that, at least for one linguistic parameter such as expressive vocabulary, persistent delay is a robust phenomenon regardless of mother tongue.…”
Section: Discussionsupporting
confidence: 80%
“…Although many LT children achieve age-appropriate scores on standardized batteries by the age of 3-5 years, others continue to lag behind on a number of language milestones, as well as reading and academic challenges [18,19,20,21,22]. Specifically, language outcomes during the preschool years indicated significant progress for lexical development but impaired morphological, phonological and syntactic skills [23,24,25,26,27,28,29,30]. The main body of research on LT toddlers comes from English language data.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Thomadaki and Stephany (2007), who studied one child, showed that 25% of the total number of nouns over the period from 1;8 to 3 ;0 were diminutives. Finally, Petinou and Okalidou (2006) compared seven Cypriot-Greek children identified as late talkers with seven aged-matched typically developing counterparts at the ages of 2;6, 2; 9 and 3;0. Although the study focused on the phonetic skills of the participants, data were also reported on expressive vocabulary assessed using a 600-word vocabulary list adapted from the CDI.…”
Section: Characteristics Of Greekmentioning
confidence: 99%
“…For instance, research findings demonstrated the robust occurrence of initial consonant deletion (ICD) in typically developing (TD) toddlers for languages including Finnish [10,11,12], Arabic [13], Estonian, and Italian [14,15]. Furthermore, data from TD Cypriot Greek (CG)-speaking toddlers revealed that the occurrence of ICD at the age of 24 months followed by long-distance regressive assimilation (RAS) was still in operation at the age of 36 months [16]. On parallel lines, data from TD toddlers suggested segmental establishment in favor of word-medial as compared to word-initial position [17].…”
Section: Introductionmentioning
confidence: 99%
“…Given the sparsity of data regarding phonological as opposed to phonetic development in CG, we sought to shed light on the developmental pattern children follow in progressing from one phonological level to the next. The focus was on examining closely and in more detail phonological process occurrence as reported in Petinou and Okalidou [16] by expanding the database and providing more cross-linguistic evidence regarding language-specific patterns with particular focus on both ICD and regressive long-distance full assimilation (harmony) of word-initial onsets to the consonant of the following syllable (RAS); e.g. /′pano/ “up” → [′ano] (= ICD) → [′nano] (= RAS) → [′pano] (= correct onset production [COP]).…”
Section: Introductionmentioning
confidence: 99%